Astrocytic Dysfunction and Addiction: Consequences of Impaired Glutamate Homeostasis. (December 2014) - Scofield, Michael D.; Kalivas, Peter W.
Addiction is characterized as a chronic relapsing disorder whereby addicted individuals persistently engage in drug seeking and use despite profound negative consequences. The results of studies using animal models of addiction and relapse indicate that drug seeking is mediated by alterations in cortico-accumbal plasticity induced by chronic drug exposure. Among the maladaptive responses to drug exposure are long-lasting alterations in the expression of proteins localized to accumbal astrocytes, which are responsible for maintaining glutamate homeostasis. These alterations engender an aberrant potentiation of glutamate transmission in the cortico-accumbens circuit that is linked to the reinstatement of drug seeking. Accordingly, pharmacological restoration of glutamate homeostasis functions as an efficient method of reversing drug-induced plasticity and inhibiting drug seeking in both rodents and humans.